Konsep, Dinamika, dan Gaya Kepemimpinan Kiai di Pesantren Salaf-Modern:: Studi Kasus PP. An-Nur 2 Malang - Edy Setiawan; Emilda Fibyani Agustin; Sultan Faiz Amrillah; Muhammad Zaironi (Universitas Al-Qolam Malang, 2026)
This study investigates the construction of Kiai leadership in navigating the dualism of the educational system at the An-Nur 2 Malang Islamic Boarding School, which integrates the Salaf (traditional) curriculum with the Modern (formal) education system. This study aims to dissect the concept, dynamics of change, and typology of leadership styles applied in maintaining turats orthodoxy while responding to the demands of modernity. Through a qualitative case study approach, the study found that the concept of leadership at An-Nur 2 no longer relies solely on a single charismatic authority, but has metamorphosed into